Creative Designs Studio Enterprise / Mohammad Azizul Mohd Noor - Bakar @ Mohd Noor, Mohammad Azizul (2020)
Regarding to fulfill the course of Fundamentals of Entrepreneurship (ENT300) requirement, I need to carry out a case study. During a case study, I require to collect all information about a company to complete this task, so I decided to contact with the owner of Creative Designs Studio Enterprise to deal an interview session with him. From the interview session, I get some information about their company such as business background, types of business product or services and many more. The overview of this case study is that I am able to see the real life situation where how a business is running through the process.